Sustainable Green Synthesis of ZnO Photocatalysts Using Shallot Peel Extract as Capping Agent for Efficient Photodegradation of Rhodamine B - Didi Prasetyo Benu; Cindy Claudia Christanti; I Gede Arya Wiguna; Fry Voni Steky; Veinardi Suendo (Jurnal Kartika Kimia, 2026)
Green synthesis strategies offer a sustainable approach for preparing semiconductor photocatalysts with tunable properties. In this study, ZnO particles were synthesized using shallot peel extract, and their structural, morphological, optical, and photocatalytic properties were systematically investigated. Structural characterization by Raman spectroscopy and X-ray diffraction confirmed the formation of phase-pure wurtzite ZnO, with crystallite sizes in the nanometer range. Scanning electron microscopy revealed hexagonal rod-like morphologies with dimensions of 1–2 μm, which are interpreted as polycrystalline assemblies of aggregated nanocrystallites. Optical analysis using UV–Vis diffuse reflectance spectroscopy showed a direct bandgap of 3.02 eV and additional visible-light absorption, which may be associated with defect states and possible extrinsic contributions. Photoluminescence spectroscopy exhibited green emission attributed to intrinsic defects. The photocatalytic performance of the synthesized ZnO was evaluated through the removal of Rhodamine B under irradiation, achieving a maximum removal efficiency of 97.68% within 150 min. Kinetic analysis indicated that the process follows a pseudo-first-order model with an apparent rate constant of 0.0290 min⁻¹. The observed photocatalytic performance may be associated with the structural and optical characteristics of the synthesized ZnO. However, the specific roles of these factors, as well as the contribution of adsorption, cannot be conclusively distinguished in the absence of a control sample. Overall, this study provides insight into the relationship between synthesis conditions and the resulting properties of green-synthesized ZnO, while highlighting the need for further investigation to clarify the underlying mechanisms. This work demonstrates that shallot peel extract is an effective and environmentally benign capping agent for engineering ZnO photocatalysts with high efficiency for wastewater treatment applications.